THE ISLAMIC CULTURE INTEGRATION AND THE LOCAL CULTURE IN THE WEDDING AT DISTRICT OF BUNTU BATU ENREKANG REGENCY - Sunardi Sunardi; Syamsudduha Saleh; Indo Santalia (Pascasarjana UIN Alauddin Makassar, 2022)
The main problem rises is how is the existence of the Islamic culture integration and the local culture in the wedding at District of Buntu Batu Enrekang Regency. This research aims to know the wedding process at district of Buntu Batu Enrekang Regency which is inside integrated between the Islamic culture and the local culture. The wedding process at district of Buntu Batu Regency of Enrekang as the result of Islamic Culture Integration and the local culture produces the wise local values that shine the Islamic element. This research uses a qualitative method which is based on the field research by conducting a historical approach, sociology, anthropology and phenomenology. The result appoints that an encounter between the Islamic culture and the local culture in the recycling of people’s life still in acculturation process namely on birth’s rites and the demise also something joins into the integration level that is in the wedding rites.